Synthesis, Characterization and Anti-Inflammatory Study of New Heterocyclic Coumarin Derivatives - Muthanna S. Farhan1 , Maadh H. Ahmed1 (Indian Journal of Forensic Medicine & Toxicology, 2021)
The inflammation is one of the most central processes in animal cells defense versus certain injuries orinfections of microbes. The most essential metabolic precursor for many inflammatory pathways is PGH2(prostaglandin), which catalytic synthesis from the AA (arachidonic acid) by COX enzymes. COX can bedivided in to three isomer COX-1 has important role in many physiological function like hemostasis, plateletaggregation, and protection of gastric mucosa, COX-2 when stimulate cause formation of PGE2 excessively,with other prostaglandin then decrease the pain threshold and nerve ending sensitization, which inducepain, increase permeability of vascular and then enhance the inflammatory associated diseases pathway, andCOX-3 has special characteristic, its higher sensitivity to acetaminophen and present in brain. The NSAIDsare therapeutic agents used for the treatment of inflammation, pain, and fever, they work by decreasing theproduction of prostaglandins due to inhibiting the function of the cyclooxygenase (COX) enzyme, we havetwo types nonselective and selective COX-2 inhibitors. In order to design new agents with no or low sideeffect, the COX-2 selectivity should be increased, this achieved by design molecule structurally similar toapproved selective COX-2 inhibitors. The synthetic compound in this study contain three pharmacophores,a nucleus of coumarin and substituted oxazole moiety, separated by a hydrazonoethyl spacer, which havestructural similarity properties to selective COX-2 inhibitors.